Durabilitas Ketahanan Varietas Padi terhadap Penyakit Tungro - R. Heru Praptana; Ahmad Muliadi (Puslitbang Tanaman Pangan, 2013)
Tungro is a damaging rice disease, especially in endemic area. Infection of tungro is caused by the infection of two different viruses, namely RTSV and RTBV, both can only be transmitted by green leafhopper. Tungro epidemic is influenced by the variety planted, tungro virus, green leafhopper, environmental conditions and cultivation practices. Resistant varieties play an important role in controlling tungro epidemic. The use of resistant varieties is an effective control component and environmentally friendly. Planting a resistant variety with different sources of genes for resistance prevent the build up of tungro epidemic. The availability of several resistant varieties is the main requirement for the sustainable management of tungro disease control. Durable resistant variety is important to be maintained, so that a comprehensive control management system based on the biology and epidemiology of tungro can be applied. Resistant variety could be developed through the incorporation of multiple genes for resistance to viruses and to vectors. The resistant varieties should be widely adopted by farmers in the endemic area. Mapping of the distribution of tungro resistant variety is required to facilitate the monitoring of varietal resistance durability to support the future resistance breeding program.